Ferroptosis in Pulmonary Disease and Lung Cancer: Molecular Mechanisms, Crosstalk Regulation, and Therapeutic Strategies - Dandan Guo; Songhua Cai; Lvdan Deng; Wangting Xu; Sentao Fu; Yaling Lin; Tong Jiang; Qing Li; Zhijun Shen; Jian Zhang; Peng Luo; Bufu Tang; et al. (MedComm)
ABSTRACT Ferroptosis is a distinct form of iron‐dependent programmed cell death characterized primarily by intracellular iron accumulation and lipid peroxidation. Multiple cellular processes, including amino acid metabolism, iron metabolism, lipid metabolism, various signaling pathways, and autophagy, have been demonstrated to influence the induction and progression of ferroptosis. Recent investigations have elucidated that ferroptosis plays a crucial role in the pathogenesis of various pulmonary disorders, including lung injury, chronic obstructive pulmonary disease, pulmonary fibrosis, and asthma. Ferroptosis is increasingly recognized as a promising novel strategy for cancer treatment. Various immune cells within the tumor microenvironment, including CD8+ T cells, macrophages, regulatory T cells, natural killer cells, and dendritic cells, have been shown to induce ferroptosis in tumor cells and modulate the process through the regulation of iron and lipid metabolism pathways. Conversely, ferroptosis can reciprocally alter the metabolic environment, leading to the activation or inhibition of immune cell functions, thereby modulating immune responses. This paper reviews the molecular mechanism of ferroptosis and describes the tumor immune microenvironment, discusses the connection between ferroptosis and the tumor microenvironment in lung cancer and pulmonary diseases, and discusses the development prospect of their interaction in the treatment of lung cancer and pulmonary diseases.